Nilai-Nilai dalam Permainan Tradisional Banjar “Ba-u-upauan” sebagai Sumber Belajar Ilmu Pengetahuan Sosial - Noor Hidayati (ENTITA: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2021)
The success of education makes students better than before. The determining factor in the success of education is supported by the personality of the students. Personality is obtained by character values ​​that are instilled through the learning process. Through this learning resource, the traditional game "Ba-u-upauan" is considered capable of shaping the personality and fostering positive values ​​of students. The aims of this research are (1) the traditional Banjar game "Ba-u-upauan" (2) the values ​​of the traditional game "Ba-u-upauan" as a learning resource for Social Sciences. This research uses descriptive qualitative research. The research subjects were the Principal, vice principal, Teachers and students. Data collection techniques were carried out through observation, interviews and documentation. The data analysis uses qualitative analysts. The result of the research is to describe the traditional Banjarese game "Ba-u-upauan" with the stages of the game starting with preparation, process and closing. The traditional Banjar game "Ba-u-upauan" has independence and togetherness which eventually raises character values, namely honest values, religious values, responsibility values, cooperation values, curiosity values, hard work values, democratic values, communicative values ​​and love values. peace that can be used as a reference in Social Science learning resources at the elementary school level.